Genetic variation in transmembrane 6 superfamily member 2 and the risk of nonalcoholic fatty liver disease and histological disease severity - Sookoian, Silvia; Castaño, Gustavo O.; Scian, Romina; Mallardi, Pablo; Fernández Gianotti, Tomas; Burgueño, Adriana L.; San Martino, Julio; Pirola, Carlos J. (Hepatology (Baltimore, Md.), 2015)
We explored the role of transmembrane 6 superfamily member 2 (TM6SF2) rs58542926 C/T nonsynonymous (p.Glu167Lys) variant in genetic susceptibility to nonalcoholic fatty liver disease (NAFLD) and disease severity. A total of 361 individuals (135 control subjects and 226 patients with histologically proven NAFLD) were included in a sample with 97% power for the additive genetic model. A discrete trait analysis of NAFLD showed that rs58542926 was associated with a modest risk of fatty liver (P = 0.038; odds ratio [OR]: 1.37; 95% confidence interval [CI]: 1.02‐1.84); nevertheless, conditioning on patatin‐like phospholipase domain‐containing 3 (PNPLA3)‐rs738409 abolished this effect. We did not observe an interaction between rs738409 and rs58542926 variants on the risk of NAFLD. We observed a significant association of rs58542926 and disease severity (P = 0.027), but not lobular inflammation or fibrosis; rs58542926 was not associated with levels of liver enzymes. An allelic test showed that the T (Lys167) allele was significantly associated with disease progression (P = 0.021; OR, 1.66; 95% CI: 1.08‐2.55). A significant association was found with the histological degree of liver steatosis (β, 0.15; standard error: 0.06; P = 0.0299) that was independent of rs738409. Homozygous carriers of the C (Glu167) allele showed increased risk for cardiovascular disease. TM6SF2 protein expression was decreased markedly in liver of NAFLD patients, compared to controls. In addition, TM6SF2 immunoreactivity was reduced in subjects carrying at least one copy of the T allele, consistent with a difference in liver allele‐specific transcript abundance. Conclusion: rs58542926 is a low‐frequency variant with a modest effect on NAFLD, suggesting that carriers of the T allele are slightly more likely to accumulate fat in the liver and develop nonalcoholic steatohepatitis than those without. TM6SF2 appears to play a significant role in disease biology. (Hepatology 2015;61:515‐525)